Effectiveness of the E-Tilang Program by the Traffic Unit of Cirebon City Police in Enforcing Traffic Violations - Sejati, Kurnia Asri (Advances in Police Science Research Journal, 2024)
The background to this problem arises because the number of traffic violations prior to the enactment of the E-Ticket program has a high number and after the enactment of the E-Ticket program decreased. Although after the enactment of the E-ticketing program the number of violations has not decreased over the last three years, but the difference from year to year does not show a significant number as before the enactment of the E-Trafficing program. As for the purpose of the research is to describe the effectiveness of the E-Traffic program in the implementation enforcement of traffic violations and find out the factors that influence the implementation of the E-ticketing program in the implementation of traffic violations. Theories and concepts for analyzing the focus of research include the Law Enforcement Effectiveness Theory and Routine Activity Theory. The concept used is the concept of E-ticket. The systematic research method is a qualitative approach. This type of research is descriptive research. Data sources consist of primary and secondary. Data collection techniques with interviews, observation, and document review. Research location at Cirebon Police Traffic Unit. The results of the study found that the E-ticket program still had many obstacles in its implementation. Therefore, the authors analyze the constraints using the theory of law enforcement and routine activity theory. The conclusion in the implementation of the E-Ticket Program is that the E-Ticket Program cannot be run optimally. Constructive advice includes suggestions to further optimize the implementation of counseling to the community regarding the procedures for the E-Traffic program and to complement the lack of facilities and infrastructure for members and to conduct socialization to the community by the Dikyasa Unit to comply with traffic regulations and introduce the E-Traffic program mechanism.